1
GATE ECE 2009
+2
-0.6
If X=1 in the logic equation $$\left[ {X + Z\left\{ {\overline Y + (\overline Z + X\overline {Y)} } \right\}} \right]$$ $$\left\{ {\overline X + \overline Z (X + Y)} \right\} = 1,$$ then
A
Y=Z
B
Y= $${\overline Z }$$
C
Z= 1
D
Z= 0
2
GATE ECE 2007
+2
-0.6
The Boolean expression Y= $$\overline A \,\overline B \,\overline C \,D + \overline A BC\overline D + A\overline {B\,} \overline C \,D + AB\overline C \,\overline D$$
A
Y = $$\overline A \,\overline B \,\overline C \,D + \overline A B\overline C + A\overline C D$$
B
Y = $$\overline A \,\overline B \,\overline C \,D + BC\overline D + A\overline B \overline C \,D$$
C
Y=$$\overline A \,BC\,\overline D + \overline B \,\overline C D + A\overline B \overline C \,D$$
D
Y= $$\overline A \,BC\,\overline D + \overline B \,\overline C D + AB\overline C \,\overline D$$
3
GATE ECE 2006
+2
-0.6
The point p in the following figure is stuck- at-1. The output f will be
A
$$\overline {AB\overline {C\,} }$$
B
$$\overline A$$
C
$$AB\overline C$$
D
A
4
GATE ECE 2004
+2
-0.6
The Boolean expression AC + B$$\overline C$$ is equivalent to
A
$$\overline A \,C + B\overline C + AC$$
B
$$\overline B C\, + AC + B\overline C + \overline A C\overline B$$
C
AC+$$B\overline C + \overline B C + ABC$$
D
$$\overline A \,B\,\overline C + A\,B\,\overline C + A\overline {\,B} \,C$$
EXAM MAP
Medical
NEET